The Transformation of Indonesian Criminal Law: Examining the Integration of Restorative Justice and Customary Institutions in the New Criminal Code - Dheny Wahyudhi; Herlambang Herlambang; Elly Sudarti (Journal Of Social Science (JoSS), 2025)
The global criminal law phenomenon shows a paradigm shift from retributive logic to restorative justice, along with increasing recognition of pluralism in local norms and values. In Indonesia, this change is embodied in Law No. 1 of 2023 on the Criminal Code, which will come into effect on January 2, 2026, and affirms the mission of decolonization, modernization, and harmonization of criminal law. However, the integration of the formal norms of the new Criminal Code and customary law through restorative mechanisms raises critical questions regarding legal certainty, criminal responsibility, and victim protection. This study uses normative legal research, with analysis of the text of the law, judicial decisions, and customary law literature. The results of the study show that the recognition of customary institutions in the restorative process strengthens social recovery and community involvement, but at the same time raises normative challenges such as inconsistent sanctions, low accountability, and the potential for local bias. This study concludes that an objective regulatory framework is needed, such as accreditation of customary institutions, minimum procedural guidelines, and sentencing guidelines, so that this integration can guarantee the principles of justice, legal certainty, and criminal accountability. This study contributes theoretically to the discourse on legal pluralism and provides practical policy recommendations for legislators and judicial institutions.